(untitled) (Rome, 2000)
This publication does not cover interrelationships between fish and mangrove, fish in salt marshes and tidal flats, use of aquatic marcrophytes as food or fish feed additives in aquaculture, fish in ricefields, use marcrophytes for the removal of aquaculture effluents and in recirculating fish culture systems. Several topics are covered only briefly: water-borne disease control( only those larvivorous and molluscivorous fish, which also serve as food, are discussed); biomanipulation ( the section dealing with this subject focuses largely on the function of fish vercus macrophytes); floodplains( the reader is directed to major publications on this topic). Control of aquatic macrophytes is limited to the use of fish, and to the impact on fish of chemical and mechanical control measures
Keywords: Fish-culture; Feeds and feeding